2013
DOI: 10.1016/j.janxdis.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and conflict behavior between veterans and their intimate partners

Abstract: This study examined the influence of trauma history and PTSD symptoms on the behavior of veterans and their intimate partners (287 couples; N = 574) observed during conflict discussions and coded using the Rapid Marital Interaction Coding System (Heyman, 2004). Dyadic structural equation modeling analyses showed that PTSD was associated with more frequent displays of hostility and psychological abuse and fewer expressions of acceptance and humor in both veterans and their partners. Findings provide new insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 68 publications
(91 reference statements)
4
71
2
2
Order By: Relevance
“…Consistent with prior studies (Elbogen et al, 2010;Karam et al, 2013;Miller et al, 2013;Pietrzak et al, 2011a,b), veterans with PTSD reported greater severity of comorbid depression, anxiety, somatization, and hostility symptoms; increased likelihood of suicidal ideation; poorer physical and mental functioning; and lower quality of life than veterans without PTSD. That veterans with the dissociative subtype of PTSD could be further differentiated from Table 4 Clinical characteristics, functioning, and quality of life of veterans with and without PTSD and the dissociative subtype of PTSD (N ¼ 1268) veterans without the dissociative subtype of PTSD on some of these clinical measures accords with prior work, which similarly found that dissociative symptoms were associated with higher levels of depression, anxiety, and hostility (Armour et al, 2014a;Stein et al, 2013;Wolf et al, 2012a).…”
Section: Any Dissociative Symptom Depersonalization a Derealization Bsupporting
confidence: 83%
“…Consistent with prior studies (Elbogen et al, 2010;Karam et al, 2013;Miller et al, 2013;Pietrzak et al, 2011a,b), veterans with PTSD reported greater severity of comorbid depression, anxiety, somatization, and hostility symptoms; increased likelihood of suicidal ideation; poorer physical and mental functioning; and lower quality of life than veterans without PTSD. That veterans with the dissociative subtype of PTSD could be further differentiated from Table 4 Clinical characteristics, functioning, and quality of life of veterans with and without PTSD and the dissociative subtype of PTSD (N ¼ 1268) veterans without the dissociative subtype of PTSD on some of these clinical measures accords with prior work, which similarly found that dissociative symptoms were associated with higher levels of depression, anxiety, and hostility (Armour et al, 2014a;Stein et al, 2013;Wolf et al, 2012a).…”
Section: Any Dissociative Symptom Depersonalization a Derealization Bsupporting
confidence: 83%
“…Frequency and intensity scores were combined to form a total severity score for each symptom, which were summed to create a total current PTSD severity score. A prior study with this dataset reported high inter-rater reliability for the CAPS (Miller et al, 2013). …”
Section: Methodsmentioning
confidence: 73%
“…In this study, two 10-minute conflict discussions between the veterans and partners were video-recorded for coding (for more information regarding the conflict discussion and coding procedures, see Miller et al, 2013). The RMICS codes of distress-maintaining and relationship-enhancing attributions were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Another assessment issue concerns the use of questionnaires instead of clinical interviews. Only two studies [28, 29] investigated PTSD in partners by means of (semi-)structured clinical interviews. Both studies found prevalence lower than 20 % although one of them [28] was conducted in a clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies [28, 29] investigated PTSD in partners by means of (semi-)structured clinical interviews. Both studies found prevalence lower than 20 % although one of them [28] was conducted in a clinical sample. This indicates that questionnaire over-estimate the prevalence of PTSD in partners of veterans.…”
Section: Discussionmentioning
confidence: 99%